Accurate segmentation of breast tumors using AE U-net with HDC model in ultrasound images. (February 2022) - Yan, Yu; Liu, Yangyang; Wu, Yiyun; Zhang, Hong; Zhang, Yameng; Meng, Lin
Highlights: Segmentation algorithms based on deep neural network achieve good results in medical images. U-net used in medical imaging segmentation but the accuracy rate needs to be improved. Propose Attention Enhanced U-net based on U-net to highlight salient features. Apply three groups of HDC with expansion rates of [1, 2, 5] in AE U-net to reduce spatial information loss. Abstract: Breast cancer poses a great threat on women health due to its high malignant rate. In China, ultrasound screening is the commonly-used method for breast cancer diagnosis, and the localization and segmentation of the lesions in ultrasound images are helpful for breast cancer detection. In this paper, an Attention Enhanced U-net with hybrid dilated convolution (AE U-net with HDC) model was proposed and employed to segment the breast tumors in ultrasound images. First, based on Attention U-net, we added a new loss function to update the weight matrix in the AGs module, in order to enhance the weight of the lesion area. Combined with fine-tuning training method, the precision of breast ultrasound image lesion region segmentation was improved from 82.38% to 86.28% and the M-IOU was improved from 76.27% to 81.81%. Second, three groups of HDC with expansion rates of [1, 2, 5] were integrated into AE U-net to replace the four convolution operations. HDC module brought larger receptive field and reduced the loss of spatial information. The experimental results proved that HDC module was helpful to improve the Acc of image segmentation results from 94.18% to 95.81% and the Recall from 78.69% to 80.48%. Combined with U-net, the F1 score, AUC, Acc and M-IOU of the network proposed in this paper had significantly improved. It proved that AE U-net with HDC model would have very important research value and application prospect for modern medicine.